Steganographic method of acoustic information protection in critical applications systems - Oleksandr Mozhaiev; Yurii Gnusov; Oleksandr Manzhai; Volodymyr Strukov; Vitalii Nosov; Valery Radchenko; Serhii Yenhalychev (Сучасний стан наукових досліджень та технологій в промисловості)
The subject of the study is the process of protecting acoustic information in critical computer systems to ensure the required level of system security. The purpose of the article is to study the method of protecting acoustic information in critical computer systems by means of masking to ensure the impossibility of unauthorized access to the system. The paper outlines the following tasks: to analyze the software and hardware masking of speech; to study the masking of speech messages in order to introduce unrecognizability; to consider the features of speech message compression; to investigate methods of covert transmission of acoustic information. The results of the work, which were obtained using mathematical methods of information transformation in computer systems, are potentially possible methods of masking speech messages to ensure the impossibility of unauthorized access to the system. The analysis of the functioning of the proposed methods made it possible to formulate specific conclusions. The research has shown that the use of direct expansion of the spectrum of discrete signals for steganographic purposes helps to covertly embed information messages in still images. The task of extracting a message on the receiving side of a steganography system is equivalent to the task of detecting information from a mixture of a useful signal and an interference in a broadband communication system.  The research revealed certain disadvantages of steganographic systems with an expanded spectrum of discrete signals: the probability of correct extraction of embedded data depends on the amount of distortion introduced, which depends on the provided bandwidth of the steganographic channel. Further research is desirable to analyze the possible use of methods for synthesizing large ensembles of quasi-orthogonal discrete signals with improved ensemble, structural, and correlation properties to ensure higher security of acoustic channels in computer systems for critical applications.